Pengaruh penambahan kacang hijau (Vigna radiata (l.) R. Wilczek) pada fermentasi susu oleh lactococcus lactis nbrc 12007 - Raras Ahlul Widawati; Endah Retnaningrum (Jurnal Teknosains, 2022)
The high content of α-galactooligosaccharide in mung beans has the potential for supporting the growth of Lactic Acid Bacteria (LAB), therefore it can be developed as fermented plant-based milk that substituted Ultra High Temperature (UHT) milk. The purposes of this research is to investigate the effectiveness of LAB Lactococcus lactis NBRC 12007 in the fermentation process of mung bean milk and to observe the quality differences of fermented mung bean milk with UHT milk.  Previously, preparations were made for starter L. lactis NBRC 12007 in MRSB medium and then sub cultured to UHT milk. Furthermore, 3% of the culture was inoculated into each of the mung bean milk substrate and UHT milk as a starter for the fermentation process and incubated for 24 hours at 37oC. During this process, the effectiveness of LAB was tested (total cell, total acid, total protein, pH, antibacterial) and the quality test of fermented products (organoleptic and physical).  Based on total cells, total acid, total protein, pH, and antibacterial test findings, fermented mung bean milk products had a higher value than UHT milk products. During the process, it was proven that L. lactis NBRC 12007 had high effectiveness in producing and improving the quality of fermented mung bean milk compared to UHT milk. It is assumed that the content of oligosaccharides supports the growth of LAB and the fermentation process.